Transitivity and Urgency in UNEP’s COP28 Climate Discourse: A Systemic Functional Analysis of Grammatical Metaphor - Selmane, Souheyla; Djouahi, Mammar; Liu , Chengyu (Al-Qanṭara, 2025)
To respond to the climate crisis, it is not enough to produce scientific evidence; the way climate action is written and spoken about also shapes how urgent and unavoidable it feels. In this study we analyse the official COP28 Production Gap Report 2023 book, treating it as a key example of UNEP’s climate discourse. Using a Systemic Functional Linguistics approach,we clause-coded the entire report for process types, participant roles, circumstantial elements and four kinds of grammatical metaphor (nominalisation, verbalisation, adverbialisation and rank-shifting). The analysis shows that relational and material processes work together to present climate change both as a fixed state of affairs and as an unfolding course of action. Carriers and Actors are the most frequent participant roles, while purpose-, location-, manner- and time-related circumstances repeatedly tie actions to specific goals, places and deadlines such as “by 2030”. Dense patterns of nominalisation and adverbialisation, often combined with rank-shifting, compress long causal chains into compact targets and pathways, and distribute agency across governments, sectors and abstract entities like “systems” or “trajectories”. Taken together, these linguistic resources create an “action grammar of urgency” that makes rapid transition appear necessary, time-bound and administratively manageable. The findings highlight how the language of the COP28 book itself can support more persuasive and responsible climate communication, and offer practical cues for policymakers and authors who draft similar reports.